DEVELOPMENT AND VALIDATION OF AN LC-MS/MS METHOD FOR DETERMINATION OF ATORVASTATIN IN HUMAN PLASMA - Prem Kumar Bichala; Lakshmana Rao Atmakuri; Vijay Kotra (Asian Journal of Medicine & Health Sciences, 2021)
Background: A novel method for the estimation of Atorvastatin in human plasma by using LCMS/MS and the analyte is Atorvastatin and internal standard is Rosuvastatin have extracted with the tertbutyl methyl ether: n-hexane (70:30, v/v) from human plasma. Methods: The chromatographic severance was attained of the peak using Agilent Zorbax Eclipse XDB-C8, (100 mm X 4.6 mm, 3.5 µm) column with a run time is 2.5 min. Atorvastatin and Rosuvastatin were recorded at the total ion current of their relevant multiple reaction monitoring. The LC-MS/MS system composed an Agilent 1100 infinity combined with an AB Sciex Qtrap4000 Thermo Finnigan TSQ quantum discovery triple quadrupole mass spectrometer. All of the parameters must be validated like selectivity, accuracy, precision, linearity, lower limit of quantification, matrix effect, recovery reached the acceptance criteria under the following ICH guidelines. Results: Atorvastatin has checked the various stability studies like short-term stability at 25 oC, long-term stability for 55 days at -70oC, wet extract stability for 54 hours, autosampler stability for 63 hours, benchtop stability for 14 hours and, freeze-thaw stability at -60 oC. Hence, it can be used for routine drug analysis and bioequivalence studies of Atorvastatin in human plasma samples. Conclusion: The proposed LC-MS/MS method was simple, rapid, precise and accurate for the determination of Atorvastatin in human plasma. The developed LC-MS/MS method can apply for the bioequivalence and pharmacokinetic studies of Atorvastatin in human plasma samples